Forecast the moisture ratio removal during seaweed drying process using solar drier - Javaid, A. (American Institute of Physics Inc., 2019)
Carrageenan was utilized in food and non-food industry such as emulsifier, pharmaceuticals, cosmetics, printing and textile formulations. However, there are underutilized efforts to develop model using mathematical and statistical techniques; the present paper explains the forecast using best model for the moisture ratio removal of seaweed drying in v-Groove hybrid solar drier under the climatic conditions of Malaysia. This study examined the effects of the interaction between the main factors. Five variables were considered in this study. Four independent variables were considered in this study namely temperature chamber (X1), humidity chamber (X2), solar radiation (X3) and collector efficiency (X4). Multiple regression models were used, the interaction up to the third level and considering 32 potential models. Each model is tested with multicollinearity test and test coefficient with the objective of removing variables that were not significant. It is concluded that mathematical modeling using eight selection criteria (8sc) would improve economic profitability of hybrid solar drier. Â© 2019 Author(s).